Analisis Pengaruh Pembelajaran Bahasa Jepang Terhadap Minat Mahasiswa Bidang Informatika Untuk Bekerja Di Jepang - Shinta Arafah Hidayanti; Syelly Nawilana Imroatus Sholikha; Iqna Raidan Abdurrahman; Nathanael Jonathan Feryanto; Bennefit Christy Saragih; Iqbal Fadhila Rachman; Hafidz Faqih Dinillah; Humannisa Rubina Lestari (Lembaga Pengembangan Kinerja Dosen, 2024)
Japanese is one of the foreign languages that is often studied by students. This research was conducted using a descriptive analysis method with a quantitative approach using correlation. The descriptive method is used to analyze the results of respondent data distributed by survey techniques using the Google From platform, and the quantitative correlation approach is used to determine the relationship between the influence of Japanese language learning on informatics students' interest in working in Japan. The subjects of this study were informatics students at the Vocational School of IPB University. The results of this study indicate a significant influence between Japanese language learning and interest in working in Japanese industries or companies by 64.3% with an average questionnaire percentage of 59.5%.